História de Roma Antiga. Vol II Império e Romanidade Hispânica - Francisco de Oliveira (Ensino, 2020)
The volume covers a temporal spectrum broad ranging from Augustus to the end of the Western Roman Empire, an organized chronologically following dynasties, statesmen, crises and times of transition, culminating in the deposition of the last emperor and in attempts to recapture vain by Justiniano.Estão present cultural values ​​and identity elements that have shaped Europe, as far as the historical legacy, institutions, values, and also a gallery of "famous men" .In the call political history, stand out other aspects that inform companies and the city spread across headings, as manifestations of culture that fits the literature, playful elements, armies and economia.